Cerebrovascular endothelin‐1 hyper‐reactivity is associated with transient receptor potential canonical channels 1 and 6 activation and delayed cerebral hypoperfusion after forebrain ischaemia in rats. (4th June 2015) - Johansson, S. E.; Andersen, X. E. D. R.; Hansen, R. H.; Povlsen, G. K.; Edvinsson, L.
Abstract Aim In this study, we aimed to investigate whether changes in cerebrovascular voltage‐dependent calcium channels and non‐selective cation channels contribute to the enhanced endothelin‐1‐mediated vasoconstriction in the delayed hypoperfusion phase after experimental transient forebrain ischaemia. Methods Experimental forebrain ischaemia was induced in Wistar male rats by a two‐vessel occlusion model, and the cerebral blood flow was measured by magnetic resonance imaging two days after reperfusion. In vitro vasoreactivity studies, immunofluorescence and quantitative PCR were performed on cerebral arteries from ischaemic or sham‐operated rats to evaluate changes in vascular voltage‐dependent calcium channels, transient receptor potential canonical channels as well as endothelin‐1 receptor function and expression. Results The expression of transient receptor potential canonical channels 1 and 6 in the vascular smooth muscle cells was enhanced and correlated with decreased cerebral blood flow two days after forebrain ischaemia. Furthermore, under conditions when voltage‐dependent calcium channels were inhibited, endothelin‐1‐induced cerebrovascular contraction was enhanced and this enhancement was presumably mediated by Ca2+ influx via upregulated transient receptor potential canonical channels 1 and 6. Conclusions Our data demonstrates that endothelin‐1‐mediated influx of extracellular Ca2+ activates transient receptor potential canonical channels 1 and 6 in cerebral vascular smooth muscle cells. This seems to have an important role in the enhanced cerebral vasoconstriction in the delayed post‐ischaemic hypoperfusion phase after experimental forebrain ischaemia.